The impact of anticoagulant-related bleeding on quality of life: Development of a novel measure based on perspectives from older adults - Anna L. Parks; Stacey L. Slager; Amy M. Cizik; Margaret C. Fang; Mark A. Supiano; Patti P. Katz; Daniel M. Witt (PLoS ONE, 2025)
Background Venous thromboembolism (VTE) and atrial fibrillation (AF) disproportionately affect older adults, who are at increased risk of bleeding from treatment with anticoagulant therapy. The impact of bleeding on older adults’ quality of life (QoL) is poorly understood due to the lack of a validated measure of their experience. This study’s purpose is to describe the first evidence-based steps in developing a new condition-specific patient-reported outcome measure (PROM) for the effect of anticoagulant-related bleeding on older adults’ QoL. Methods Adults aged 65 years and older with VTE or AF at the University of Utah who were eligible for anticoagulation were recruited. We purposely sampled by age, sex, race/ethnicity, diagnosis, bleeding history and anticoagulant. In accordance with evidence-based guidelines for PROM development, focus groups were conducted to refine a hypothesized conceptual model of bleeding-related QoL and analyzed according to hybrid inductive and deductive thematic analysis methods. Focus group results were used to write a draft PROM. Semi-structured qualitative interviews were conducted to revise items on the draft PROM and were analyzed using thematic analysis to generate a final bleeding-related QoL PROM. Results Twenty individuals participated in interviews, and nine in two focus groups. Median age was 81 (range 69–95), 52% were women and 69% were White (10% Asian, 10% Hispanic, 7% Black, 3% Native Hawaiian/Pacific Islander). Through inductive and deductive thematic analysis of focus groups, we identified 19 themes (e.g., specific bleeding symptoms, adaptations in relationships, fatigue) that fell into 5 domains: 1) bleeding symptoms, 2) healthcare experiences, 3) social function, 4) emotional function, 5) physical function. These 19 themes and 5 domains formed the basis of the draft PROM. We conducted semi-structured cognitive interviews, and we performed thematic analysis to revise the drafted measure for clarity and relevance. The data resulted in a new PROM for bleeding-related QoL in older adults. Conclusion Employing evidence-based methods for PROM development, we found that bleeding can have a marked impact on everyday activities, emotional wellbeing and interpersonal relations for older adults. We incorporated these distinct aspects of wellbeing and function into a novel PROM for bleeding-related QoL that can inform clinical care and research after subsequent psychometric validation.